2013
DOI: 10.1179/1743132812y.0000000126
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis and pulmonary embolisms in adult patients undergoing craniotomy for brain tumors

Abstract: Objective The development of venothromboembolisms (VTEs), including deep vein thrombosis (DVT) and pulmonary emboli (PE), is common in brain tumor patients. Their development can be catastrophic. Studies evaluating pre-operative clinical factors that predispose patients to the development of VTE are few and limited. An understanding may help risk stratify patients and guide subsequent therapy aimed at reducing the risk of DVTs/PEs. Methods All adult patients who underwent surgery for an intracranial tumor at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 28 publications
3
69
0
1
Order By: Relevance
“…Multiple studies have reported the relationship between brain tumor grade and VTE development. Uniformly, patients with high-grade gliomas have been shown to have a higher incidence of VTE [10][11][12][13]48,53,54]. We also noted a significant association between age and grade, but not cardiovascular disease or ambulatory status.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Multiple studies have reported the relationship between brain tumor grade and VTE development. Uniformly, patients with high-grade gliomas have been shown to have a higher incidence of VTE [10][11][12][13]48,53,54]. We also noted a significant association between age and grade, but not cardiovascular disease or ambulatory status.…”
Section: Discussionmentioning
confidence: 59%
“…One of the most recent studies of DVT/VTE incidence in brain tumor patients undergoing craniotomy reports a DVT incidence of only 3.0% [48]. Higher rates of VTE/DVT in the patients in the present study (13.7%) may be a result of vigorous testing for DVT and PE at our institution during this period.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Several risk factors have previously been associated with the development of VTE in GBM patients including functional status, paresis, residual disease, obesity, chemotherapy and vascular endothelial growth factor targeted treatment [5]. It is also well established that the risk for VTE is high in the post surgical period and can extend up to 30 days after the surgical procedure [6]. However, it is unclear if an increased risk of VTE remains after the post-surgical period.…”
Section: Introductionmentioning
confidence: 97%